Useful bullshit : constitutions in Chinese politics and society - Diamant, Neil J., 1964- (Cornell University Press, 2021)
"Examines what happened when the Chinese government encouraged millions of its citizens to read, listen to, and pose questions about drafts of new constitutions, and the implications of such constitutional talk for how we understand political legitimacy and the origins of constitutionalism. Drawing on multiple archival sources from the Maoist and reform eras, as well as insights from the philosophy of language, this book provides new interpretations of the role of law in China, popular constitutionalism, and the legitimacy of the Communist Revolution from the perspective of those who experienced it"--